Measuring the Maturity Level of Social Assistance Distribution Data Governance Using the 2019 Cobit Framework - Endra, Robby Yuli; Rizal, Usman; Afandi, Freddy Nur (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2024)
This study aims to measure the maturity level of data governance in the distribution of social assistance using the COBIT 2019 framework. We chose COBIT 2019 as the methodology due to its comprehensive guidance for information technology governance. Measurements were made by assessing researchers focused on 4 domains APO, BAI, and DSS. The results of the study indicate variations in the level of maturity across processes. Some processes, such as risk management and operational efficiency, have reached the desired level of maturity, while other processes, such as information security and organizational change management, still require significant improvement. The gaps found in this measurement provide valuable insights into areas that require further attention. Recommendations for improvement include improving user training, strengthening security procedures, and improving communication and stakeholder engagement. Implementation of the proposed improvements is expected to improve data governance maturity and, in turn, improve the quality and accuracy of social assistance distribution. This study makes a significant contribution to understanding and improving data governance in the public sector, especially in the context of social assistance distribution. The results and recommendations from this study can be used by related organizations to optimize their data management processes so that they can be more effective and efficient in serving the public.